2013
DOI: 10.4314/ijbcs.v7i3.39
|View full text |Cite
|
Sign up to set email alerts
|

Survenue des obstructions tubaires chez les femmes à Cotonou (Bénin) : rôle des bactéries

Abstract: Les trompes utérines jouent un rôle très important dans la reproduction humaine. Elles peuvent être facilement atteintes par diverses pathologies dont l'obstruction tubaire. La présente étude a permis de déterminer le taux d'obstructions tubaires dues aux infections et de relever les bactéries en cause à Cotonou. Pour ce faire, 111 femmes venues pour hystérosalpingographie (HSG) ont été soumises aussi à des prélèvements sanguins et cervicaux (bilans microbiologiques). Au total, 51,3% de femmes souffrent d'obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
1
1
0
1
Order By: Relevance
“…Myomas accounted for more than 77% of all causes of uterine origin. This figure is very close to that found by Gandji et al [13] who found 76.8% of causes of infertility linked to myomas, especially submucosal.…”
Section: Discussionsupporting
confidence: 91%
“…Myomas accounted for more than 77% of all causes of uterine origin. This figure is very close to that found by Gandji et al [13] who found 76.8% of causes of infertility linked to myomas, especially submucosal.…”
Section: Discussionsupporting
confidence: 91%
“…Les fluoroquinolones (ofloxacine, ciprofloxacine) avaient l'activité la plus faible vis-à-vis des souches de U. urealyticum (15%) ; cette activité était moyenne sur les souches de M. hominis (59% et 63%). (Karou et al, 2012 ;Gandji et al, 2013 ;Diaz et al, 2013 ;Diop-N'diaye et al, 2014 ;Xiaofei et al, 2016). Ces résultats sont contraires à celui de Ouégnin et al 2008 (Waites et al, 2012).…”
Section: Sensibilité Aux Antibiotiquesunclassified
“…The combined frequency of Mycoplasma hominis and Ureaplasma urealyticum in vaginal swabs was 7% in a 2009 study conducted in Burkina Faso [7]. In Benin, 35.1% of people tested positive for mycoplasma [8]. It was discovered that 71.4% of women living with Human Immunodeficiency Virus (HIV) in Cameroon also had mycoplasma infections [9].…”
Section: Introductionmentioning
confidence: 99%